Occupational and Environmental Hazards of Correctional Settings: A Scoping Literature Review From ACOEM's Presidential Task Force on Correctional Institutions. Issue 3 (March 2022) - Montoya-Barthelemy, Andre; Gibson, Brent R.; Lee, Charles D.; Bade, Aashia M.; Butler, James W.; Smith, Eric; Skipworth, Diane; Gutekunst, Julie; Segula, Marjorie Naila; Wicken, Cassie; Friedman, Eric; Darbari, Isha; et al.
Abstract : Objective: Maintaining healthful, safe, and productive work environments for workers in correctional settings is a matter of deep consequence to the workers themselves, the institutions they serve, the incarcerated individuals with whom they share space, and inevitably, to our wider community. We hypothesized that an examination of the academic literature would reveal opportunities for an improved approach to research in these settings. Methods: We performed a scoping literature review using search terms related to the occupational and environmental health of workers in correctional environments, limited to studies performed in the United States. Results: A total of 942 studies underwent title and abstract screening, 342 underwent full-text review, and 147 underwent data extraction by a single reviewer. The results revealed a body of literature that tends strongly toward analyses of stress and burnout of correctional staff, largely based on self-reported data from cross-sectional surveys. Those studies related to physical health were predominantly represented by topics of infectious disease. There were few or no studies examining exposures or outcomes related to diagnosable mental health conditions, musculoskeletal injury, environmental hazards, medical or mental health staff, immigration detention settings, or regarding incarcerated workers. There were very few studies that were experimental, longitudinal, or based on objective data. Discussion: The National Institute for Occupational Safety and Health (NIOSH) has promulgated a research strategy for correctional officers that should guide future research for all workers in correctional settings, but realization of these goals will rely upon multidisciplinary collaboration, specific grants to engage researchers, and an improved understanding of the barriers inherent to correctional research, all while maintaining rigorous protection for incarcerated persons as an especially vulnerable population.